Development of E-modules Based on PjBL-STEAM and Virtual Simulation Media on Work and Energy Topic as an Effort to Improve Students’ Critical Thinking Skills - Rafidah, Farah; Parno, Parno; Nasikhudin, Nasikhudin; Ali, Marlina (Jurnal Pendidikan Sains, 2024)
Work and energy are fundamental topics in physics. However, enhancing students’ critical thinking skills in these areas remains a challenge. This research aimed to develop and assess the validity and readability of e-modules designed with PjBL-STEAM and virtual simulation media to address this issue. The development process followed a 4D model, and the resulting e-modules were evaluated as strongly valid category. The validation tests yielded percentage scores of 91.6% for media, 89.3% for content, and 88.0% for lesson plans. Additionally, the readability test achieved a score of 84.6%, indicating a excellent level of comprehensibility. These findings suggest that the e-modules based on PjBL-STEAM with integrated virtual simulation media are well-suited for use in physics education, particularly for improving students’ critical thinking skills.DOI: 10.17977/jps.v12i32024p093